Impact of N-Acyl-Homoserine Lactones, Quorum Sensing Molecules, on Gut Immunity - Coquant, Garance; Grill, Jean-Pierre; Seksik, Philippe (Frontiers in Immunology, 2020)
Among numerous molecules found in gut ecosystem, Quorum Sensing (QS) molecules represent an overlooked part that warrants highlighting. QS relies on the release of small molecules (auto-inducers) by bacteria that accumulate in the environment depending on bacterial cell density. These molecules are sensed by the microbial community but also interact with host cells and contribute to gut homeostasis. It therefore appears entirely appropriate to highlight the role of these molecules on the immune system in dysbiosis associated inflammatory conditions where the bacterial populations are imbalanced. Here, we intent to focus on one of the most studied QS molecule family, namely the type I auto-inducers represented by N-acyl-homoserine lactones (AHL). First described in pathogens such as Pseudomonas aeruginosa, these molecules have also been found in commensals and have been recently described within the complex microbial communities of the mammalian intestinal tract. In this mini-review, we will expound on this emergent field of research. We will first recall evidence on AHL structure, synthesis, receptors and functions regarding inter-bacterial communication. Then, we will discuss their interactions with the host and particularly with agents of the innate and adaptive gut mucosa immunity. This will reveal how this new set of molecules, driven by microbial imbalance, can interact with inflammation pathways and could be a potential target in inflammatory bowel disease (IBD). The discovery of the general impact of these compounds on the detection of the bacterial quorum and on the dynamic and immune responses of eukaryotic cells opens up a new field of pathophysiology.